2011
DOI: 10.1073/pnas.1101818108
|View full text |Cite
|
Sign up to set email alerts
|

Two synaptobrevin molecules are sufficient for vesicle fusion in central nervous system synapses

Abstract: Exocytosis of synaptic vesicles (SVs) during fast synaptic transmission is mediated by soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex assembly formed by the coil-coiling of three members of this protein family: vesicle SNARE protein, synaptobrevin 2 (syb2), and the presynaptic membrane SNAREs syntaxin-1A and SNAP-25. However, it is controversially debated how many SNARE complexes are minimally needed for SV priming and fusion. To quantify this effective number, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
138
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(168 citation statements)
references
References 45 publications
25
138
0
Order By: Relevance
“…In the first model, we suggest that although the threshold occurs at 23-30 sybs on the entire surface of the liposome this is the total amount required to locally enrich SNARE complexes, a process that implies stronger coupling and time synchronization in the cooperative assembly of the SNARE complexes. We have modeled a possible scenario and found that two to four SNARE complexes assembled in synchrony would fit in between two large liposomes as contact between membranes is initiated, in agreement with in vivo studies (12,15,33). However, we caution that this is a lower bound estimate because we cannot rule out lateral diffusion of neighboring SNAREs.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In the first model, we suggest that although the threshold occurs at 23-30 sybs on the entire surface of the liposome this is the total amount required to locally enrich SNARE complexes, a process that implies stronger coupling and time synchronization in the cooperative assembly of the SNARE complexes. We have modeled a possible scenario and found that two to four SNARE complexes assembled in synchrony would fit in between two large liposomes as contact between membranes is initiated, in agreement with in vivo studies (12,15,33). However, we caution that this is a lower bound estimate because we cannot rule out lateral diffusion of neighboring SNAREs.…”
Section: Discussionmentioning
confidence: 80%
“…Whether and how SNAREs cooperate to mediate fusion has been a subject of intense study, with estimates ranging from a single SNARE complex to 15. Here we show that there is no universally conserved number of SNARE complexes involved as revealed by our observation that this varies greatly depending on membrane curvature.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…In summary, the possible explanations for the partial effect observed with siRNA assays might be (a) molecular redundancy, that is, the protein levels remaining after knockdown are high enough to maintain their normal functionality; 27,55,56 (b) functional redundancy, that is, other VAMP members can substitute for the knockdown; 47 or (c) a combination of the two previous hypotheses. However, the results obtained with TeNT-LC and with VAMP2-ΔTMD lead us to prefer the functional redundancy hypothesis, if we assume that almost all detectable VAMP2 (and VAMP3) proteins were proteolyzed, as was observed by WB.…”
Section: Discussionmentioning
confidence: 99%